Effects of Aerobic Exercise on The Six Minutes Walking Test and Quality of Life in EGFR Mutation Non-Small Cell Lung Cancer Patients - Sibarani, Lia Priscilia; Setijadi, Ana Rima; Apriningsih, Hendrastutik; Harsini , Harsini; Raharjo, A. Farih; Sutanto, Yusup Subagio (Jurnal Respirologi Indonesia, 2025)
Background: Lung cancer reduces lung function, muscle mass, and psychological well-being, which lowers exercise capacity and quality of life. Pulmonary rehabilitation, such as aerobic exercise, can improve exercise capacity and the quality of life (QoL) in lung cancer patients. This study aimed to investigate the influence of aerobic exercise on the six-minute walking test (6MWT) and the quality of life of lung cancer patients. Methods: A clinical trial with a quasi-experimental, pretest, and post-test design was conducted on stage ≥IVa adenocarcinoma lung cancer patients who were receiving outpatient targeted therapy at the pulmonary clinic of Dr. Moewardi General Hospital for ≥1 month starting from May 2023, until the required sample size was met. The 6MWT and Functional Assessment of Cancer Therapy-Lung (FACT-L) were measured at the baseline and eight weeks ±2 weeks after aerobic exercise by walking about 15-20 minutes and breathing exercises. Results: The study included fourteen patients in the control group and fifteen patients in the aerobic group. The mean difference of 6MWT between the control and the aerobic group was 38.33 m. Functional, lung cancer subscale (LCS), total, and TOI in FACT-L showed significant differences in the increment pre-test and post-test between the control and aerobic group (P<0.05), with significant differences in pre-test and post-test of most categories in both groups, except for social. Conclusion: Aerobic exercise, psychological support, and nutrition have significantly improved the 6MWT and quality of life in lung cancer patients.